Pengaruh Kompetensi, Profesionalisme, Dan Tekanan Waktu Terhadap Kualitas Audit Dengan Teknologi Informasi Sebagai Pemoderasi - Juslen justinus Sihombing; Amrie Firmansyah (Owner : Riset dan Jurnal Akuntansi, 2025)
This research examines the influence of competence, professionalism and time pressure on the quality of investigative audits by applying information technology as a moderator. This research uses a quantitative method using primary data and the selection of respondents is based on purposive sampling with the criteria of of auditors at The Audit Board of the Republic of Indonesia (1) having conducted an investigative examination in order to calculate state losses, (2) having a Certified Fraud Auditor (CFrA) and Certified Fraud Examiner (CFE) certification, (3) fulfilling the education and training hours per year at the Directorate General of Investigative Unit of the BPK RI. The data used in this research came from a questionnaire survey distributed to respondents from October 23 th -26th 2023. The final sample used in this study amounted to 78 observations. The research tested competence, professionalism has a positive effect on the quality of investigative audits, while time pressure has a negative effect on the quality of investigative audits and the application of information technology as a moderator strengthens the effect of competence, and professionalism on the quality of investigative audits, and weakens the negative effect of time pressure on the quality of investigative audits. This research contributes to the literature on investigative auditing and suggests improving auditor competence and professionalism and using information technology in conducting investigative audits